Myiasis in a neglected and immunocompromised middle aged patient: a rare case report (Bangladesh Journal of Medical Science, 2026)
Maggot (Dipteran larva) infection in living tissue is termed as Myiasis. It is found to be most common in tropical countries in rural and suburban locations, involving populations of low socioeconomic strata and immunocompromised neglected patients. Traumatic or wound myiasis involving skin is the most common site, however it may involve other sites like oral, nasal, intestinal and urogenital system etc. We are reporting here a case of 51 years old male, who had previous history of untreated diabetes mellitus and currently presented with an ulcerated lesion over upper back which was infested with maggots. Excision of the mass was done and a diagnosis of chronic maggot infection (Myiasis) was rendered histologically. The determinants of infestation were immunocompromised status due to poor glycaemic control, ignorance and improper wound care. Myiasis is a preventable complication and care needs to be taken for prompt treatment and more awareness about the disease.BJMS, Vol. 25 No. 02 April’26 Page: 655-658